En klaverstil folder sig ud: Niels Viggo Bentzons klavermusik i 1940’erne og 1950’erne - Krarup, Bertel (Danish Yearbook of Musicology, 2000)
During the 1940s and 1950s Niels Viggo Bentzon, being both a composer and a pianist, developed an original and personal piano style. It is a style in which a considerable amount of romantic expressivity is often added to the tonal and Hindemith-inspired Neoclassicism. The composer’s method of working, in which the borderline between improvisation and composition is fluid, gives some of the works a sense of ‘frozen improvisation’. The main aim of the article is to describe the development in Niels Viggo Bentzon’s piano style through the examination of some central works, such as Toccata op. 10 (1941), Passacaglia op. 31 (1944), Partita op. 38 (1945), the sonatas nos. 2 to 6 (1946-52), and Træsnit op. 65 (1951). The article concludes with an outline of the time after 1960 when the developing form of the earlier works yields to a more tessellated structure.